Teaching Materials Development in the Scope of Islamic Education Research in Indonesia: A Systematic Literature Review - Dluha, A. Yulian Syamsudl; Masithoh, Arina Dewi; Rizqiyah, Afi (Jurnal Penelitian Pendidikan Islam, 2024)
A literature review serves to determine trends in a field of research so that further research gaps can be found. This study aims to conduct a literature review on the development of teaching materials in the scope of Islamic Education in Indonesia in the last ten years. This research is a qualitative type with a Systematic Literature Review approach. Data collection followed David Moher's PRISMA procedure consisting of identification, screening, eligibility, and included stages. Followed by the extraction and mapping of articles using Vosviewer software before being analyzed. The research findings show that the teaching materials developed are mostly in the form of printed teaching materials such as books, LKS, encyclopedias, modules, and scrapbooks. Only one teaching material is a video. The development model applied is still limited to the Borg & Gall, ADDIE, and Jerol E. Kemp models. The majority of teaching material development has standard objectives such as increasing learning motivation, understanding, and student learning outcomes. However, there is also interesting content such as scientific integration, literacy, and religious moderation. Based on these findings, the research gap related to the development of Islamic Education teaching materials is still wide. The development of teaching materials can be collaborated with the use of technology, content about Islamic education, and effective learning models.